2021
DOI: 10.3390/ijerph18168476
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Residential Exposure to Particulate Matter and Its Components, Nitrogen Dioxide and Ozone—A Northern Sweden Cohort Study on Mortality

Abstract: This study aims to estimate the mortality risk associated with air pollution in a Swedish cohort with relatively low exposure. Air pollution models were used to estimate annual mean concentrations of particulate matter with aerodynamic diameter ≤ 2.5 µm (PM2.5), primary emitted carbonaceous particles (BC/pOC), sea salt, chemically formed particles grouped as secondary inorganic and organic aerosols (SIA and SOA) as well as ozone (O3) and nitrogen dioxide (NO2). The exposure, as a moving average was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…The entire NO 2 association takes place at concentrations below the EPA NO 2 annual standard and again, other recent literature has also reported associations in that range ( Wei et al, 2021 ; Ma et al, 2022 ; Schwartz et al, 2021b ; Crouse et al, 2015 ). Previous results for O 3 have been mixed, as were ours ( Yazdi et al, 2021b ; Cakmak et al, 2018 ; Sun et al, 2022 ; Sommar et al, 2021 ). In general, studies in North America have reported positive effects of O 3 , while studies in Europe have found negative, protective effects.…”
Section: Discussioncontrasting
confidence: 67%
“…The entire NO 2 association takes place at concentrations below the EPA NO 2 annual standard and again, other recent literature has also reported associations in that range ( Wei et al, 2021 ; Ma et al, 2022 ; Schwartz et al, 2021b ; Crouse et al, 2015 ). Previous results for O 3 have been mixed, as were ours ( Yazdi et al, 2021b ; Cakmak et al, 2018 ; Sun et al, 2022 ; Sommar et al, 2021 ). In general, studies in North America have reported positive effects of O 3 , while studies in Europe have found negative, protective effects.…”
Section: Discussioncontrasting
confidence: 67%
“…However, there are also studies reported null associations between those components with mortality [ 22 , 23 ]. Some studies have examined NO 3 − , SO 4 2− , NH 4 + together as secondary inorganic aerosols (SIA) and shown associations with cardiovascular mortality but not with all-cause and respiratory mortality [ 24 , 25 ]. Our study also reported a general pattern of greater mortality rate ratio magnitudes for cardiovascular mortality than all non-accidental and respiratory mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of our study is that we have stronger study power by incorporating all deaths in Massachusetts from 2000 to 2015. Many previous studies on long-term PM 2.5 components exposures were cohort studies that identified several thousand deaths during the follow-up [ 18 , 23 , 24 ], or up to tens of thousands of cases [ 17 , 25 ]. In our study, we have included nearly 800 thousand deaths, which provided a much stronger study power than the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…4 Figures 3 and 4 show the mortality results of other recent European studies for long-term PM 2. 5 8-15 and NO 2 , [11][12][13][14][15][16][17][18][19] respectively, which were published after the closing dates of the WHO systematic reviews. The results from these studies are compared with the summary estimates from the WHO systematic reviews (red vertical line) and the summary estimate from the ELAPSE study.…”
Section: Mortality Estimates From Recent European Studiesmentioning
confidence: 99%